Mechanism of improvement and best-fit models for the prediction of geotechnical properties of lime stabilized expansive soil used in pavement subgrade - Muhammad Ali Naveed; Sarfraz Ahmed; Arshad Ullah; Muhammad Danish Zia (Mehran University Research Journal of Engineering and Technology, 2024)
The performance of a pavement mainly depends on the quality of the subgrade layer. Expansive soils (ES) are extensively found worldwide including Pakistan. The inadequate strength and swelling behaviour of these soils are the main problems in any road construction project. Several researchers in the last decades have attempted to improve expansive soil utilizing various materials such as lime, brick kiln dust and fly ash. The purpose of this research was to evaluate the effect of lime on the engineering properties of the ES of a highway subgrade in the Sialkot region of Pakistan. The influence of different lime dosages (0%, 2%, 4% and 6%) at curing ages (1, 7, 14 and 28 days) has been examined by pH tests, plasticity tests, compaction tests, unconfined compressive strength (UCS), free swell index, and California Bearing Ratios (CBR). A field CBR and plate load test (PLT) on the natural soil and optimum lime-treated soil with various curing periods have been carried out for applicability as subgrade material. The test findings demonstrated that higher lime dosages increased the strength and ultimate bearing capacity (𝑞𝑢𝑙𝑡) of improved ES and at the same time decreased the free swelling index (FSI), optimum moisture content (OMC), maximum dry density (MDD) and permanent deformation of the subgrade soil. The UCS values of soil treated with 2%, 4% and 6% lime increased almost by 324%, 523%, and 249% for unsoaked samples and 285%, 351% and 231% for soaked samples respectively as compared to the plain soil at 28 days curing period. The laboratory CBR values significantly increased 2.35-8.50 times and field CBR improved 5.6 times as compared to the plain soil. The 𝑞𝑢𝑙𝑡 of lime-treated soil increased by 162% as compared to the plain soil and permanent deformation reduced from 33 mm to 2 mm after 28 days. Furthermore, equations were developed to estimate the best fit for the prediction of various geotechnical parameters and coefficient of determination (R2 ) values for all equations were found higher than 0.90. From the results, it has been concluded that adding the optimum lime content of 4% by weight satisfies the requirement for the subgrade construction of highways and the developed expressions can provide a scientific basis for estimating the geotechnical parameters.